Multiphase flow 1995 : proceedings of the Second International Conference on Multiphase Flow, Kyoto, Japan, April 3-7, 1995 - Serizawa, Akima; Fukano, T. (Tohru), 1940-; Bataille, Jean, Dr (Elsevier Science, 1995)
There is increasing world-wide interest in obtaining an understanding of various multiphase flow phenomena and problems in terms of a common language of multiphase flow. This volume contains state-of-the-art papers which have been contributed from all over the world by experts working on all aspects of multiphase flows. The volume also highlights international technology-sharing in the fields of energy, environment and public health, in order to create a brighter and sustainable future for man and for all life in the next century. It is intended that this volume will serve as a major source of literature for the advancement of multiphase flow and allied fields.